STRATEGI PEMASARAN DALAM MENINGKATKAN PENJUALAN PRODUK TAWAS HILYA DI BANYUGLUGUR SITUBONDO - Nur Imama; Sri Ayudha Mujiyanti; Lusi Endang Sri D (LPPM Politeknik Pratama, 2025)
This study aims to determine the 4P marketing strategy for Tawas Hilya products and to determine Shopee's role in increasing sales of Tawas Hilya products. The approach used in this study is a qualitative approach. Data were collected through direct observation, in-depth interviews with business owners, employees and several consumers, as well as documentation of product packaging. The results of the study indicate that Tawas Hilya products have good quality in terms of packaging, brand, and logo. The price of Tawas Hilya is also very affordable considering the size and weight of the product. Tawas Hilya products are known and their sales have increased because they are sold through the Shopee application by sharing Shopee sales links on various social media platforms, including Facebook, Instagram, and WhatsApp.